State Housing-Choice Vouchers as a Solution to the Housing Crisis: Potential Vulnerabilities and Possible Alternatives - Dufour, River (Maine Policy Review, 2024)
Considering the inadequacies of the federal housing choice voucher program, and the dire conditions in which eligible families are living, legislators have argued that Maine should supplement the federal voucher program with a state-run housing- choice voucher program (hereafter referred to as State 8). This year, multiple bills were introduced with this intention, the broadest being LD 1710— An Act to Establish the Maine Rental Assistance and Guarantee Program and Amend the Laws Regarding Tenants and the Municipal General Assistance Program. Despite all being carried over into the next legislative session, this kind of program has significant support and will likely continue to be championed by some legislators in the coming years. In this commentary the author explores the potential viability of such a program and consider the vulnerabilities of this strategy for addressing the housing crisis in Maine.